Reifying women's experiences with invisible illness : illusions, delusions, reality - Williams, Kesha Morant; Morant, Frances Selena (Lexington studies in health communication., 2017)
This book provides an alternative to narratives that privilege the biomedical perspective on women's invisible illnesses. The contributors include women who exude diversity as it relates to race and ethnicity, career, religious experience, education, social support, and interpersonal relationships.